(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Small islands are an entity that has limitations to be used. This study aimed to analyze the land carrying capacity for settlement and its implication on water quality at small islands. The carrying capacity of land are determined based on an analysis of the minimum space requirements of each individual according to Indonesian National Standards (SNI) 03-1733-2004, while the implications for water quality are determined based on the nutrient load approach. The results of this research showed that the Tiworo archypelago have a total potential land approximately 198.94 ha and about 31.45 ha of this amount has been utilized. Although the land use is relatively small, however, there are also islands that have been used to exceed their carrying capacity. The human population density of each island has a positive correlation with the level of the land degradation. The total population currently is still tolerated by water bodies, but when the population is suitable with the land carrying capacity will increase the ammonia ratio by 0.086-0.550. This indicates that the land carrying capacity of the Tiworo chained Islands is not higher than the ability of the water body in assimilating the domestic waste.